Antibiotic resistome biomarkers and determinants in lettuce planting soil amended with β-lactam pharmaceutical fermentation residues - Ruiqi Wan; Kaixuan Zheng; Tianyu Chen; Yanping Xun; Jitao Lv; Lingyi Meng; Yufei Yang; Xuemei Zhu (Bioresource Technology, 2027)

Pressure-mediated mechanosensitive Piezo2 channel is activated in neurogenic bladder and promote bladder fibrosis in children - Lei Lv; Yanping Zhang; Qi Li; Junkui Wang; Shuai Yang; Zhaokai Zhou; Shuai Li; Zhengguang Zhang; He Zhang; Xingchen Liu; Yibo Wen; Jian Guo Wen (Journal of Molecular Medicine, 2026)

Effective strategy for simultaneous removal of Congo red and Cr(VI) by ferroan brucite - Shifeng Zhao; Xin Fan; Fengzhu Lv; Yanping Zhao; Yuli Cui (Journal of Water Process Engineering, 2026)

All-weather anti-salt solar desalination using a sandwich evaporator with thermal storage and asymmetric wettability - Yimin Qu; Changliang Lu; Ziyue Zhang; Xi Wen; Xuanli Jing; Tiaohong Zhang; Ting Lv; Dajian Huang; Yanping Wang; Xiaohu Qiang (Chemical Engineering Journal, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Zwitterionic nanoparticle-mediated interfacial hydration for robust, salt-rejecting, and anti-fouling solar steam generation - Jianbin Zhang; Yuhao Zhai; Zhichao Chen; Ting Lv; Dianming Li; Yanhua Liu; Yanping Wang; Wufang Yang; Baoli Ou; Libang Feng; Feng Zhou (Chemical Engineering Journal, 2026)

AutoML democratizes water quality forecasting: Lowering expertise barriers - Yangyang Chu; Yun Fang; Liangzhi Sun; Yang Zhang; Liujian Wang; XiaoMeng Han; Mou Lv; Haixing Liu; Kunlun Xin; Weigang Wang; Yanping Zhu; Shihu Shu (Journal of Water Process Engineering, 2026)

Inhibition of potato common scab by Bacillus subtilis XT11 and its reshaping of the microbial community in potato geocaulosphere soil - Ning Liu; Minghao Lv; Yongdong Wang; Huimin Ma; Wei Fan; Junjie Ma; Jiguang Wang; Yanping Gao; Jinbiao Ma; Bo Zhou; Wenchong Shi; Zheng Gao (World Journal of Microbiology and Biotechnology, 2026)

Expansion of the rhizosphere soil and phyllosphere bacterial resistomes following repeated farmland application of high-temperature granulation-treated antibiotic fermentation residues - Ruiqi Wan; Tianyu Chen; Yanping Xun; Yazhuo Chen; Jitao Lv; Lingyi Meng; Kristian Koefoed Brandt; Yawei Wang (Journal of Environmental Sciences, 2026)

Dynamic response analysis of topside transportation using SPMT - Ming Qiu; Min Zeng; Mingzhi Li; Yibin Lv; Changwei wan; Zhengang Wang; Yanping He (Ocean Engineering, 2025)

Contribution of solar photovoltaic to the decarbonization of wastewater treatment plants in China - Ranbin Liu; Yanping Qiao; Huanlun Zhang; Maokun Lv; Xiaodi Hao (Desalination, 2025)

Treatment of kiwifruit with Lactiplantibacillus pentosus CW5 cell-free supernatant maintains postharvest quality and alters the surface microbiome - Yuxuan Hao; Huili Pang; Haoxin Lv; Guofang Wu; Jianbo Zhang; Xuan Luo; Miao Zhang; Yaoke Duan; Yuting Hou; Yanping Wang; Lei Wang; Yimin Cai; et al. (Postharvest Biology and Technology, 2025)

Forest transformation increases soil N2O fluxes in an unmanaged Moso bamboo forest - Yibo Yan; Xueying Tu; Hui Zhang; Yang Lv; Yihui Zhao; Ao Hu; Yanping Wu; Caixian Tang; Yixiang Wang (Forest Ecology and Management, 2025)

Novel advanced oxidation technology of Fe2+-activated peracetic acid for high efficient disintegration of waste activated sludge - Wenqi Liu; Yanping Zhang; Jing Zhang; Ning Lv; Yibing Li (Journal of Environmental Chemical Engineering, 2024)

Promotional effect of microwave radiation treatment on the desorption of CO2 from mono-ethanolamine (MEA) solution over FeOOH catalyst - Haoran Zhang; Junge Lv; Zhibo Xiong; Huancong Shi; Jing Jin; Mengqi Liu; Yanping Du; Wei Lu (Journal of Environmental Chemical Engineering, 2024)

A prediction method for favorable hydrocarbon accumulation areas in carbonate oil reservoirs based on machine learning and driven by formation water chemical characteristic data - Zhiwei Chen; Jianbo Gao; Hong Pang; Zhipeng Huo; Ningliang Sun; Yanping Lv; Yan Wang; Bo Wu (Carbonates and Evaporites, 2024)

Effective strategy for Cr(VI) removal from water in evolution process of ferroan brucite by redox and intercalation - Shifeng Zhao; Fengzhu Lv; Yanping Zhao; Jiajing Feng; Hanxia Tang (Journal of Water Process Engineering, 2024)

Electrochemistry promotion of Fe(Ⅲ)/Fe(Ⅱ) cycle for continuous activation of PAA for sludge disintegration: Performance and mechanism - Jing Zhang; Yanping Zhang; Ning Lv; Fen Li; Yibing Li; Zhenjie Guo (Environmental Research, 2024)

AKR1C2 genetic variants mediate tobacco carcinogens metabolism involving bladder cancer susceptibility - Yanping Xiao; Yang Shen; Hui Song; Fang Gao; Zhenguang Mao; Qiang Lv; Chao Qin; Lin Yuan; Dongmei Wu; Haiyan Chu; Meilin Wang; Mulong Du; et al. (Archives of Toxicology, 2024)

Aquifer Water Abundance Evaluation Based on a Variable Weight Model - Aoshuang Mei; Qiang Wu; Keyao Han; Yifan Zeng; Pengfei Yang; Yanping Miao; Yang Lv; Yashuai Cui; Liang Yang (Mine Water and the Environment, 2024)

Synthesis of defective Ni-Mn layered double hydroxides nanosheets via alkali-assisted Mo doping for urea electro-oxidation - Ming Yang; Wanyu Ge; Zirui Liu; Qiang Yue; Jun Zhang; Yanping Lv; Hao Wu (Fuel, 2024)

Superhigh and ultrafast removal of congo red and methylene blue in the evolution process of ferroan brucite with multiple mechanism - Shifeng Zhao; Yanping Zhao; Zhiming Wu; Fengzhu Lv; Guocheng Lv; Libing Liao (Journal of Environmental Chemical Engineering, 2023)

Machine learning algorithm inversion experiment and pollution analysis of water quality parameters in urban small and medium-sized rivers based on UAV multispectral data - Yikai Hou; Anbing Zhang; Rulan Lv; Yanping Zhang; Jie Ma; Ting Li (Environmental Science and Pollution Research, 2023)

An overview of the direct and indirect effects of acid rain on plants: Relationships among acid rain, soil, microorganisms, and plants - Yan Zhang; Jiahong Li; Junyan Tan; Wenbin Li; Bhupinder Pal Singh; Xunan Yang; Nanthi Bolan; Xin Chen; Song Xu; Yanping Bao; Daofei Lv; Anan Peng; et al. (Science of The Total Environment, 2023)

Removal of chlorine, microparticles and water from high-viscosity liquids by a sand filter coupling hydrocyclone - Aosong Wei; Jianping Li; Minjie Shan; Wenjie Lv; Jianqi Chen; Pengbo Fu; Yanping Liu; Weichun Xu; Li Dai; Hualin Wang (Process Safety and Environmental Protection, 2023)

Luffa rootstock enhances salt tolerance and improves yield and quality of grafted cucumber plants by reducing sodium transport to the shoot - Zhixin Guo; Yanping Qin; Jingli Lv; Xiaojie Wang; Han Dong; Xiaoxing Dong; Tao Zhang; Nanshan Du; Fengzhi Piao (Environmental Pollution, 2023)

Citric Acid and Poly-glutamic Acid Promote the Phytoextraction of Cadmium and Lead in Solanum nigrum L. Grown in Compound Cd–Pb Contaminated Soils - Yu Wang; Weidong Duan; Chao Lv; Zhuangzhuang Wei; Yanping Zhu; Qi Yang; Ying Liu; Zhenguo Shen; Yan Xia; Kun Duan; Lingtong Quan (Bulletin of Environmental Contamination and Toxicology, 2023)

Dynamic agricultural drought risk assessment for maize using weather generator and APSIM crop models - Yaxu Wang; Juan Lv; Hongquan Sun; Huiqiang Zuo; Hui Gao; Yanping Qu; Zhicheng Su; Xiaojing Yang; Jianming Yin (Natural Hazards, 2022)

Gene–environment interaction between circadian clock gene polymorphisms and job stress on the risk of sleep disturbances - Yuxi Wang; Min Zhao; Peixin Li; Chuancheng Wu; Yanping Lv; Yu Jiang (Psychopharmacology, 2022)

An Updated Genome Assembly Improves Understanding of the Transcriptional Regulation of Coloration in Midas Cichlid - Yunyun Lv; Yanping Li; Yi Liu; Zhengyong Wen; Yexin Yang; Chuanjie Qin; Qiong Shi; Xidong Mu (Frontiers in Marine Science, 2022)
Midas cichlid ( Amphilophus citrinellus ), a popular aquarium fish, attracts extensive attention from worldwide biologists mainly due to its morphological polymorphism (dark versus gold). Continuous efforts have therefore been paid to address mechanisms of its coloration variants, while it is far away from the detailed illustration of a clear regulatory network. Some limits may come from the absence of a high-quality genome assembly and a relatively accurate gene set. In this study, we sequenced about 149 Gb of nucleotide sequences of Midas cichlid, generating a genome assembly with a total size of 933.5 Mb, which exhibits a good genome continuity with a contig N50 of 10.5 Mb. A total of 25,911 protein-coding genes were annotated and about 90% completeness was achieved, which helps to build a good gene pool for understanding expressional differences of color variation. With the assistance of the final gene set, we identified a total of 277 differential expressional genes (DEGs), of which 97 up- and 180 downregulated were determined in dark-vs-gold comparisons. Two protein-protein interaction (PPI) networks were constructed from these DEGs, and three key functional modules were classified. Hub genes within each module were evaluated, and we found that the third key module contains tyrp1b , oca2 , pmela , tyr , and slc24a5 , which were previously proven to be associated with melanin formation. Two downregulated DEGs ( myl1 and pgam2 ) in the first key module may be involved in muscle movement and spermatogenesis, implying that certain side effects could result from the morphological polymorphism. The first key module, consisting of proteins encoded by upregulated DEGs that were associated with MAPK signaling, Toll-like receptor signaling, and gonadotropin-releasing hormone pathways, may contribute to a negative upstream regulation or downstream influence on melanin biosynthesis. Taken together, our new genome assembly and gene annotation of Midas cichlid provide a high-quality genetic resource for biological studies on this species, and the newly identified key networks and hub genes in dark-vs-gold comparisons enhance our understanding of the transcriptional regulatory mechanisms underlying coloration changes not only in Midas cichlid but also in other fishes from freshwater to marine ecosystems.

Metabolomic profiling of brassinolide and abscisic acid in response to high-temperature stress - Jinhua Lv; Tianyu Dong; Yanping Zhang; Yu Ku; Ting Zheng; Haifeng Jia; Jinggui Fang (Plant Cell Reports, 2022)

Clinical features and prognostic factors of patients with COVID-19 in Henan Province, China - Qianqian Zhang; Zheng Wang; Yanping Lv; Jiang Zhao; Qiang Dang; Dongfeng Xu; Dongxiang Zhao; Haiyang Liu; Ziqi Wang; Xingru Zhao; Zhiwei Xu; Xiaoju Zhang (Human Cell, 2021)

Probiotic Potential and Wide-spectrum Antimicrobial Activity of Lactic Acid Bacteria Isolated from Infant Feces - Xing Wang; Weidong Wang; Haoxin Lv; Hua Zhang; Yuan Liu; Miao Zhang; Yanping Wang; Zhongfang Tan (Probiotics and Antimicrobial Proteins, 2021)

Microbial reduction of bromate: current status and prospects - Xinyue Lv; Dan Wang; Waheed Iqbal; Bo Yang; Yanping Mao (Biodegradation, 2019)

Detection of virus in CSF from the cases with meningoencephalitis by next-generation sequencing - Hongzhi Guan; Ao Shen; Xia Lv; Xunzhe Yang; Haitao Ren; Yanhuan Zhao; Yinxin Zhang; Yanping Gong; Peixiang Ni; Honglong Wu; Yicheng Zhu; Liying Cui (Journal of NeuroVirology, 2016)

Dopamine transporter availability in heroin-dependent subjects and controls: longitudinal changes during abstinence and the effects of Jitai tablets treatment - Ying Liu; Mei Han; Xingdang Liu; Yanping Deng; Yu Li; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Jinlong Gao (Psychopharmacology, 2013)

Genome-wide analysis of primary auxin-responsive Aux/IAA gene family in maize (Zea mays. L.) - Yijun Wang; Dexiang Deng; Yunlong Bian; Yanping Lv; Qin Xie (Molecular Biology Reports, 2010)